Heavy metal concentrations in soils and accumulation in plants growing in a deserted slag dumpsite in Nigeria (2008)
Early detection and remediation of heavy metals in soil and vegetation will ameliorate serious threats posed to human existence. An auto battery manufacturing company dumped slag containing proportion of heavy metals in an hectare of land at Lalupon, Ibadan, Nigeria. The extent of contamination of soil by heavy metals and their accumulation in plants around the abandoned slag was studied. Plants and the surrounding soils were sampled from different directions at increasing distance from the vicinity of the waste pile and their concentrations of heavy metals were determined. The levels of Pb, Zn and Ni in mg/kg ranged from 34.8 – 41500, 16.3 – 849 and ND – 48.2; 9.2 – 9700, 16.0 – 271 and 2.83 – 36.9; 4.5- 5670, 8.00 – 174 and ND – 322 in soil, plant root and plant shoot, respectively. The plant samples from the immediate environment of the waste were highly contaminated with Pb. Six plant species, particularly Sporobolus pyramidalis, met some of the conditions to be classified as hyperaccumulators for Pb, Ni and Zn, and three other plants fulfilled the criteria for heavy metal excluders. We conclude that the potential hyperaccumulators and excluders, under controlled conditions, can be used for phytoremediation of the site.